Editorial (KEMANUSIAAN The Asian Journal of Humanities, 2008)
This volume is the inaugural edition of Kemanusiaan The Asian Journal of Humanities, a publication of the Penerbit Universiti Sains Malaysia. The journal, formerly known as Jurnal Ilmu Kemanusiaan (Journal of Humanities), was first published in 1994. After 14 volumes of articles and writings by a pool of academics from the region, Asia Pacific and Europe, the challenges in the global academic scenario motivated the restructuring of the journal to make it known internationally. The reformation entailed not just the reorganisation of the physical and technical structures of the journal but also more importantly re-thinking its focus and name. Kemanusiaan, a Malay word which encapsulates humanities and being humanitarian, is appropriate as the name of the journal. Whilst the name Kemanusiaan captures the scope of the discipline, the inclusion of the word Asian in the title provides a regional focus. This makes the journal a fitting forum for academics writing on issues in the humanities in Asia as well as aspects that deal with the humanities in non-Asian contexts particularly ones that concern the relationships between the two areas. In this inaugural volume, four articles by academics from the Asia Pacific and America covering the issues of higher education, geography and philosophy are included. The first contribution is based on a study on the Malaysian Professoriate. It attempts to delineate the changes in the profession and discusses these within the current global context. The second article focuses on geomorphology and it attempts to foreground environmentally-friendly approaches to river management that have important impact on humanity. The third and fourth contributions discuss issues in the area of philosophy. In the third article, the author argues that whilst religion, ethics and the meaning of life are intertwined, those who are non-believers can still live an ethical and meaningful life in the present postmodern context. In the last article, the author argues that moral perspectives should not be limited only to "the impartial concern for all who share a common humanity with us" but also those who are "strangers to us."